2017
DOI: 10.1016/j.str.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

The Ciliopathy-Associated Cep104 Protein Interacts with Tubulin and Nek1 Kinase

Abstract: SummaryCilia are thin cell projections with essential roles in cell motility, fluid movement, sensing, and signaling. They are templated from centrioles that dock against the plasma membrane and subsequently extend their peripheral microtubule array. The molecular mechanisms underpinning cilia assembly are incompletely understood. Cep104 is a key factor involved in cilia formation and length regulation that rides on the ends of elongating and shrinking cilia. It is mutated in Joubert syndrome, a genetically he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…In the proximity maps generated for retinal degeneration-associated CCDC66 and Joubert syndrome-associated CEP104 and CEP120, proteins implicated in ciliogenesis were highly enriched. Consistent with these interactions, functional studies showed that CEP104 interacts with Nek1and functions in cilium length regulation, and CCDC66 interacts with the CEP290 and is required for cilium assembly [129,151]. Additionally, structural and interaction studies of CEP120 ciliopathy mutants defined its destabilization as a consequence of the mutations and showed that mutant cells were defective in their ability to ciliate [132].…”
Section: Primary Cilium Biogenesis and Proteomementioning
confidence: 74%
See 1 more Smart Citation
“…In the proximity maps generated for retinal degeneration-associated CCDC66 and Joubert syndrome-associated CEP104 and CEP120, proteins implicated in ciliogenesis were highly enriched. Consistent with these interactions, functional studies showed that CEP104 interacts with Nek1and functions in cilium length regulation, and CCDC66 interacts with the CEP290 and is required for cilium assembly [129,151]. Additionally, structural and interaction studies of CEP120 ciliopathy mutants defined its destabilization as a consequence of the mutations and showed that mutant cells were defective in their ability to ciliate [132].…”
Section: Primary Cilium Biogenesis and Proteomementioning
confidence: 74%
“…To date, proximity mapping has been used to mechanistically dissect these processes using both targeted and systematic approaches. As for the targeted approaches, proximity interaction maps were generated for known regulators of cilium assembly as well as proteins mutated in ciliopathies including CEP72, CCDC66, CEP104, MIB1, ARL13B, CDC14A, LUZP1 and CEP120 [122,129,130,132,[134][135][136]151]. As with centriole duplication, these maps identified new functional modules required for specific steps of cilium assembly and revealed mechanisms that underlie ciliopathies.…”
Section: Primary Cilium Biogenesis and Proteomementioning
confidence: 99%
“…S6 and Table S3 and refs. 50 and 51 ). The CEP104 and MEKK1 TOG domains both share a similar pair of arginine-rich C-terminal helices relative to canonical TOGs.…”
Section: Discussionmentioning
confidence: 99%
“…At the structural level, MEKK1 has common TOG features, but also divergence at the N-and C-termini that may facilitate its role. One close structural homolog of MEKK1 is another recently-identified TOG domain from CEP104 (Supplementary Figure 5; Supplementary Table 3; (Al-Jassar et al, 2017;Rezabkova et al, 2016)). The CEP104 and MEKK1 TOG domains both share a similar pair of additional C-terminal helices relative to canonical TOGs.…”
Section: Discussionmentioning
confidence: 99%